Persen lemak tubuh, aktivitas fisik, body image, asupan energi, asupan karbohidrat berkorelasi dengan keragaman makanan pada remaja di perkotaan - Putri Ronitawati; Nazhif Gifari; Laras Sitoayu; Putri Nurhasanah (AcTion: Aceh Nutrition Journal, 2022)
Insufficient dietary diversity in adolescents, and the amount of food consumed is small and incomplete, causing a mismatch between intake and nutritional adequacy in adolescents. The study aimed to analyze the relationship between body fat percent, physical activity, body image, energy intake, carbohydrate intake, and consumption diversity in adolescents in urban areas. The research design was cross-sectional, conducted in 10 public high schools in DKI Jakarta in July–November 2019. The sample used purposive sampling following the inclusion and exclusion criteria provisions. The sampling technique used was random so that 250 students were obtained for each school. Data collection on characteristics, nutritional knowledge, and body image, used a questionnaire that the respondents themselves filled in. Nutritional status data is collected using anthropometric measurements and determined based on BAZ. Nutrient intake data was collected using recall intake, which was measured every 1 x 24 hours, and body fat percent data was collected using an Omron BIA. Physical activity data using the International Physical Activity Questionnaire (IPAQ). Data on adolescent consumption diversity using energy and carbohydrate intake recall measured 1x24 hours. Data was analyzed using the Spearman correlation test. The results stated that there was a relationship (p<0,05) between percent body fat, physical activity, body image, calorie intake, and carbohydrate intake with dietary diversity (IDDS) in adolescents in urban areas. In conclusion, adolescent dietary diversity is related to percent body fat, physical activity, body image, energy intake, and carbohydrate intake.